Development of learning object for engineering courses in UTeM - Ummi Raba'ah, H. (2009)
This paper views e-learning initiative in UTeM with a focus on the development of learning object for engineering courses in UTeM. Having a learning management system called SPeL, UTeM further promote e-learning culture by encouraging knowledge sharing through SPeL's learning object repository. UTeM is gradually building a collection of reusable learning objects to be shared across faculties. The paper discusses the concept of learning object in UTeM context, roles of Subject Matter Expert (SME), UTeM's learning object design strategy and the development stages of learning object in UTeM. The paper further stated briefly on the benefits of learning object to UTeM.